A Theory of Brain Drain and Public Funding for Higher Education in the United States - Ionescu, Felicia; Polgreen, Linnea A (American Economic Review, 2009)
A Theory of Brain Drain and Public Funding for Higher Education in the United States by Felicia Ionescu and Linnea A. Polgreen. Published in volume 99, issue 2, pages 517-21 of American Economic Review, May 2009